c-Jun promotes neuroblastoma cell differentiation by inhibiting APC formation via CDC16 and reduces neuroblastoma malignancy - Yunyun Wang; Jingjing Huang; Zhenhua Song; Shuo Zhang; Haojie Guo; Qi Leng; Na Fang; Shaoping Ji; Jian Yang (Biology Direct)
Abstract Neuroblastoma is a pediatric embryonal malignancy characterized by impaired neuronal differentiation. Differentiation status in neuroblastoma strongly affects the clinical outcome, thus, enforcement of differentiation becomes a treatment strategy for this disease. However, the molecular mechanisms that control neuroblastoma differentiation are poorly understood. As an extensively studied protein of the activator protein-1 (AP-1) complex, c-Jun is involved in numerous cell regulations such as proliferation, survival and differentiation. In the current study, we demonstrated that c-Jun expression was upregulated by retinoic acid (RA) and flow cytometry assay indicated c-Jun overexpression arrested cell cycle to G1 phase, which, in turn, promoted the initiation of neuroblastoma cell differentiation. Co-immunoprecipitation (co-IP) assay showed that c-Jun competitively interacted with CDC16, a key subunit in anaphase-promoting complex (APC), resulting in reduced APC formation and inhibition of cell cycle progression. Furthermore, EdU proliferation assay and transwell experiment showed that c-Jun overexpression inhibited neuroblastoma cell proliferation and migration via interacting and sequestering CDC16. These findings identify c-Jun as a key regulator of neuroblastoma cell cycle and differentiation and may represent a promising therapeutic target to induce neuroblastoma differentiation via the interaction between c-Jun and CDC16.